Semiotic deconstruction of Science-Quran integration in Physics: Analysis of QS. Hud: 67 and sound waves - Imaduddin, Ihsan; Taufiq, Wildan (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to evaluate the integration of Qur’anic verses and physical science concepts in Indonesian high school physics textbooks, focusing on the interpretation of lightning through QS. Hud:67. Using a qualitative descriptive approach and critical content analysis, this research combines semiotic theory from Roland Barthes and Charles S. Peirce, alongside a comparative exegesis (tafsir muqaran) of Ibn Kathir, Al-Alusi, and Tantawi Jauhari. The findings reveal that interpreting the word ṣayḥah (الصيحة) as “sound wave” in the textbook neglects its theological and linguistic dimensions. This misinterpretation violates the principles of Qur’anic hermeneutics and constructs a myth that the Qur’an contains explicit modern scientific theories. The study concludes that a proper integration between science and Islam must be grounded in valid interpretative methodology and semiotic awareness. It offers a conceptual contribution toward developing a more rigorous, hermeneutical, and ethical model of Islam-science integration.